Alternative Oxidase Inhibitors Potentiate the Activity of Atovaquone against Plasmodium falciparum - Murphy, Anina D. (American Society for Microbiology, 1999)
Recent evidence suggests that the malaria parasite Plasmodium falciparum utilizes a branched respiratory pathway including both a cytochrome chain and an alternative oxidase. This branched respiratory pathway model has been used as a basis for examining the mechanism of action of two antimalarial agents, atovaquone and proguanil. In polarographic assays, atovaquone immediately reduced the parasite oxygen consumption rate in a concentration-dependent manner. This is consistent with its previously described role as an inhibitor of the cytochrome bc(1) complex. Atovaquone maximally inhibited the rate of P. falciparum oxygen consumption by 73% ± 10%. At all atovaquone concentrations tested, the addition of the alternative oxidase inhibitor, salicylhydroxamic acid, resulted in a further decrease in the rate of parasite oxygen consumption. At the highest concentrations of atovaquone tested, the activities of salicylhydroxamic acid and atovaquone appear to overlap, suggesting that at these concentrations, atovaquone partially inhibits the alternative oxidase as well as the cytochrome chain. Drug interaction studies with atovaquone and salicylhydroxamic acid indicate atovaquone’s activity against P. falciparum in vitro is potentiated by this alternative oxidase inhibitor, with a sum fractional inhibitory concentration of 0.6. Propyl gallate, another alternative oxidase inhibitor, also potentiated atovaquone’s activity, with a sum fractional inhibitory concentration of 0.7. Proguanil, which potentiates atovaquone activity in vitro and in vivo, had a small effect on parasite oxygen consumption in polarographic assays when used alone or in the presence of atovaquone or salicylhydroxamic acid. This suggests that proguanil does not potentiate atovaquone by direct inhibition of either branch of the parasite respiratory chain.